Emerging developments in the standardized chemical characterization of indoor air quality. (January 2017) - Nehr, Sascha; Hösen, Elisabeth; Tanabe, Shin-ichi
Abstract: Despite the fact that the special characteristics of indoor air pollution make closed environments quite different from outdoor environments, the conceptual ideas for assessing air quality indoors and outdoors are similar. Therefore, the elaboration of International Standards for air quality characterization in view of controlling indoor air quality should resort to this common basis. In this short review we describe the possibilities of standardization of tools dedicated to indoor air quality characterization with a focus on the tools permitting to study the indoor air chemistry. The link between indoor exposure and health as well as the critical processes driving the indoor air quality are introduced. Available International Standards for the assessment of indoor air quality are depicted. The standards comprise requirements for the sampling on site, the analytical procedures, and the determination of material emissions. To date, these standardized procedures assure that indoor air, settled dust and material samples are analyzed in a comparable manner. However, existing International Standards exclusively specify conventional, event-driven target-screening using discontinuous measurement methods for long-lived pollutants. Therefore, this review draws a parallel between physico-chemical processes in indoor and outdoor environments. The achievements in atmospheric sciences also improve our understanding of indoor environments. The community of atmospheric scientists can be both ideal and supporter for researchers in the area of indoor air quality characterization. This short review concludes with propositions for future standardization activities for the chemical characterization of indoor air quality. Future standardization efforts should focus on: (i) the elaboration of standardized measurement methods and measurement strategies for online monitoring of long-lived and short-lived pollutants, (ii) the assessment of the potential and the limitations of non-target screening, (iii) the paradigm shift from event-driven investigations to systematic approaches to characterize indoor environments, and (iv) the development of tools for policy implementation. Highlights: We propose priority areas for future standardization related to indoor air quality. Standards for online monitoring of long-lived and short-lived pollutants Assessment of the potential and the limitations of non-target screening Paradigm shift from event-driven investigations to systematic IAQ studies Development of tools for policy implementation